How Can Legal Politics Advance Environmental Justice? A Case Study of Illegal Sea Sand Mining in Babi Island, Karimun, Riau Islands - Baskoro, Aji (Universitas Sumatera Utara, 2025)
Illegal sea sand mining poses significant challenges to environmental justice, particularly in Indonesia’s coastal regions. This research is motivated by the urgency to understand and evaluate legal policies to address the complexities of issues arising from sea sand mining activities. The study explores how environmental legal policies are applied to regulate and mitigate the impacts of illegal sea sand mining. Additionally, it examines the consequences of illegal mining on environmental justice, particularly concerning coastal ecosystem degradation and the livelihoods of local communities. Despite the existence of regulatory instruments such as Government Regulation No. 26 of 2023 on Marine Sedimentation Management and Law No. 32 of 2009 on Environmental Protection and Management, enforcement remains inadequate, allowing persistent violations that exacerbate ecological damage and social inequities. This study employs a normative legal method with a statutory and case study approach, analyzing secondary data from legal documents, academic literature, and media reports. Thematic, policy, and case analyses reveal significant implementation gaps, weak enforcement mechanisms, and insufficient community participation in environmental governance. The findings indicate that while existing legal frameworks provide a foundation for sustainable resource management, systemic weaknesses and fragmented governance hinder their effectiveness in preventing illegal activities. This research recommends strengthening regulatory enforcement, enhancing community empowerment through environmental education, and integrating sustainability principles into policy implementation. Additionally, fostering multi-stakeholder collaboration is crucial for addressing governance challenges and ensuring the equitable distribution of environmental benefits and risks. These strategies aim to promote environmental justice and sustainable coastal management in Indonesia.